Antibody reactivity against Helicobacter pylori proteins in a sample of the Spanish adult population in 2008‐2013. Issue 5 (24th July 2017) - Fernández‐de‐Larrea, Nerea; Michel, Angelika; Romero, Beatriz; Butt, Julia; Pawlita, Michael; Pérez‐Gómez, Beatriz; Castaño‐Vinyals, Gemma; Moreno, Victor; Martín, Vicente; Amiano, Pilar; Castilla, Jesús; Fernández‐Tardón, Guillermo; et al.
Abstract: Background: Differences in Helicobacter pylori protein expression have been related to the risk of severe gastric diseases. In Spain, a marked geographic pattern in gastric cancer mortality has long been reported. Objective: To characterize antibody reactivity patterns against 16 H. pylori proteins, by age, sex, and region of birth, in a large sample of the Spanish adult population. Materials and Methods: Antibody reactivity was quantified by H. pylori multiplex serology in a sample from the control group of the multicase‐control study MCC‐Spain. For this analysis, 2555 population‐based controls were included. Each participant was classified as seropositive or seronegative for each protein according to specific cutoffs. Overall H. pylori seroprevalence was defined as positivity against ≥4 proteins. Descriptive analyses by age, sex, and region of birth were performed for both seroprevalence and seroreactivity (continuous measure). Differences among groups were tested by logistic and linear regression models. Results: Overall H. pylori seroprevalence increased with age in both sexes. For ages 55‐74, seroprevalence was lower in women than in men (84% vs 92%, P <.001). Region of birth explained 7% of the variability in seroprevalence. Among H. pylori seropositive subjects, proteins with the highest seroprevalence were GroEL, NapA, HP231, and Omp. Seropositivity for most of the proteins increased or remained stable with age, rising mainly for CagA, GroEL, and HyuA in women. A clear cohort effect was not observed. Conclusions: This is the first study to describe the antibody patterns against 16 H. pylori proteins in the Spanish population. We found variability in the H. pylori antibody profiles according to both individual factors such as age and sex, and environmental factors such as the region of birth. The slightness of the reduction in seropositivity with decreasing age highlights the ongoing importance of this infection.